2006
DOI: 10.1142/s0218539306002094
|View full text |Cite
|
Sign up to set email alerts
|

On Using Soft Computing Techniques in Software Reliability Engineering

Abstract: Previous investigations have shown the importance of evaluating computer performances and predicting the system reliability. This paper considers soft computing techniques in order to be used for software fault diagnosis, reliability optimization and for time series prediction during the software reliability analysis. It is shown that the study of the data collections during a software project development can be done within a soft computing framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 20 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Application of Soft Computing techniques in software reliability engineering has come up recently (Madsen et al, 2006). Despite the recent advancements in the software reliability growth models, it was observed that different models have different predictive capabilities and also no single model is suitable under all circumstances.…”
Section: Literature Surveymentioning
confidence: 99%
“…Application of Soft Computing techniques in software reliability engineering has come up recently (Madsen et al, 2006). Despite the recent advancements in the software reliability growth models, it was observed that different models have different predictive capabilities and also no single model is suitable under all circumstances.…”
Section: Literature Surveymentioning
confidence: 99%
“…With this development of NHPP as the base, several methodologies have been coming into existence which includes Gompetz [5], S-shaped Distribution [6], [7] and Inversed S-Shaped distribution [8]. Particular models like Jelinski and Moranda model [9], Littlewood & Verrall model [10], Goel -Okumoto model [11], Musa -Okumoto model [12], Kuo, Huang, & Lyu [13], Brown DB [14], Kapur PK [15], Khan, Ahmad and Rafi [16], Ohishi, Okamura and Dohi [17], Satya Prasad, Naga Raju and Kantam [18], Zou and Davis [19], Kiyoshi, Henrik and Poul [20] etc., are also highlighted in the literature with the aim, optimizing the errors in the developed software's. However, these, models are effectual when the errors are estimated most apparently and have a complete overview of discriminating between failure and non-failure.…”
Section: Introductionmentioning
confidence: 99%
“…Application of soft‐computing techniques in place of statistical techniques has come up in the recent years in software reliability engineering . Kiran and Ravi proposed software reliability prediction using soft‐computing techniques.…”
Section: Introductionmentioning
confidence: 99%